THE EFFECT OF AL-KAHIL AND AL-AKHADAIN POINT CUPPING THERAPY ON REDUCING CHOLESTEROL LEVELS - Nurul Qomariah; Grido Handoko; Dodik Hartono (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
Hypercholesterolemia is a condition where the increase in total cholesterol concentration in the blood exceeds the normal limit. High cholesterol levels can lead to blockage (atherosclerosis). Cholesterol treatment can be carried out by pharmacological or non-pharmacological namely complementary.the purpose of the study was to determine the effect of al- kahil and al- akhdain point swelling theraphy on reducing cholesterol levels in the holistic nursing clinic of probolinggo theraphy. This type of research is pre-experimental, with a study design of one group pre-post test design. The sample of this study was 35 patients with normal high and high cholesterol levels that were taken by accidental sampling instrument which used observation sheets and GCU easy touch tools,data collection includes coding editing and tabulating then the data is analyzed manually with a computer with a paired sample test analysis test . The results of the univariate study showed that the average results before cupping therapy at the al-kahil and al-akhdain was of 233.26 mg/dl and the standard deviation of 11.748. Average cholesterol levels after cupping therapy at the al-kahil and al-akhdain was199.83) mg / dl and a standard deviation of 14,639. analysis of the results of the study using a paired sample test obtained p - value = 0.000 < a = 0.05. The conclusion from the analysis test results obtained that there was an effect of cupping therapy point Al - Kahil and Al - Akhdain on the reduction of cholesterol levels at the Holistic Nursing Therapy Clinic in Probolinggo. This research can be used as an ingredient to improve the quality of services especially in lowering cholesterol levels an an alternative treatmentTraditional effective for the healing process of high cholesterol levels with Al - Akhil and Al - Akhdain point cupping therapy.